Physiological and biochemical responses of twelve autochthonous grapevine varieties to summer stress in the Douro Demarcated Region - Gaspar, Maria; Carvalho, Márcia; Baltazar, Miguel; Ferreira, Helena; Valente, Joana; Alves, Fernando; Castro, Isaura; Gonçalves, Berta (Frontiers in Plant Science, 2026)
Grapevine (Vitis vinifera L.) is one of the most cultivated crops in Portugal and worldwide and plays an important role in the Mediterranean countries’ economies. In the last decade, this region has faced increasing summer stress that negatively impacts plant growth and development and reduces crop’s yield and quality. These challenges can be addressed by exploring grapevine varietal diversity to identify promising genotypes capable of coping with summer stress. In this study, twelve different autochthonous varieties grown in the Douro Superior sub-region from the Douro Demarcated Region were studied in two different phenological stages (veraison and maturity) and two consecutive growing seasons (2023 and 2024). Measurements included leaf gas exchange parameters (in the morning and midday), lipid peroxidation analysis, determination of the contents of photosynthetic pigments, total soluble sugars, starch, bioactive compounds - including total phenolics, flavonoids, and ortho-diphenols -, and of the antioxidant activity using ABTS, DPPH, and FRAP assays. The data obtained revealed that ‘Tinta Roriz’ and ‘Alicante Bouschet’ presented photosynthetic activity, water use efficiency and pigment levels, suggestive of tolerance to summer stress. On the other hand, ‘Mourisco de Semente’, ‘Malvasia Preta’, and ‘Touriga Fêmea’ revealed lower antioxidant activity, and photosynthetic capacity, indicative of higher vulnerability to stress conditions. The remaining varieties presented an intermediate summer stress tolerance or a growing season-tolerance variability. These findings highlight the diversity of responses of different grapevine varieties to summer stress and reinforce the importance of identifying stress-resilient genotypes.